Understanding perceptions of teachers and pupils towards corporal punishment for pupils with disabilities in primary schools in Tanzania: Implications for the promotion of social justice in education - Zuberi, Thabiti; Seni, Abdallah Jacob; Sungwa, Reuben (Universitas Majalengka, 2025)
In Tanzanian primary schools, corporal punishment is legally permitted and widely practiced as a disciplinary method, often extending to pupils with disabilities. This study explores the perceptions of teachers and pupils towards the use of corporal punishment on pupils with disabilities, focusing on its implications for social justice and inclusive education. A qualitative approach, employing a phenomenological design, was used to understand the lived experiences of the participants. Data were collected through in-depth interviews with two head teachers and eight subject teachers, as well as focus group discussions involving ten pupils with disabilities, all purposively sampled. Thematic analysis revealed that corporal punishment is commonly justified by teachers as a means of addressing indiscipline, despite its negative impact on pupils’ emotional well-being and academic engagement. Some teachers recognized the contradiction between corporal punishment and inclusive education principles, highlighting its violation of the rights of pupils with disabilities. Pupils described feeling marginalized and fearful, highlighting the adverse effects of this practice on their sense of belonging and learning environment. The study recommends a shift towards alternative disciplinary approaches that uphold the rights and dignity of all pupils, particularly those with disabilities. It emphasizes the need for targeted professional development programs to equip teachers with non-violent strategies for managing classroom behavior. Furthermore, it calls for the enforcement of inclusive education policies and the creation of support networks to foster socially just and equitable learning environments. By addressing these issues, this study contributes to the discourse on inclusive education and social justice, advocating for systemic reforms to align Tanzanian educational practices with global standards.